Biologia de anofelinós amazônicos. VII. Estudo da variação de freqüências das inversões cromossômicas de Anopheles darlingi Root (Diptera, Culicidae) () - Tadei, Wanderli Pedro; Santos, Joselita Maria Mendes dos (Acta Amazonica, 1982)
Three samples of natural populations of Anopheles darlingi from Km 175 of BR-174 Highway (Manaus/Boa Vista) are here analysed concerning the frequency of the inversions. Two samples were collected during the rainy period and a third one in the dry season. The results showed a highly polymorphic character of the Anopheles darlingi Amazonia populations and also modifications of the genetic variants, during the samplings. There were changes, in different levels, in the frequencies of the inversions of the three pairs of chromosomes and also as to the frequencies of the three asynapsed regions, one being in chromosome X and two in chromosome 2. Tests of intra and interchromo-somic inversion association were male and the checking of the results of each test, in the three samples simultaneously, showed that the same association is not present in two or three samplings at the same time These changes in different periods were seen as result of a rearrangement in the structure of the genetic composition of the populations because of environmental modifications. High frequencies of heterozygotes (near or above 50%) were observed in most of the inversions, but In different levels depending on the inversion and the period of sampling. The mean number of inversions, per individual, in the heterozygote state, also changed during the periods, the highest rate being observed in the rainy season. The results were discussed in relation to the heterogeneity of the Amazonia forests and the species adaptation strategy. The hypothesis the cariotipic constitution of the species could interfere in the parameter of the vector capacity of the species is also discussed.